Reinterpretation of the Jilbab Concept in Contemporary Islamic Education: A Study of Muhammad Shahrur’s Hudud Theory - Mutiara, Sri (CV. Tripe Konsultan, 2025)
The obligation to wear the jilbab (Islamic veil) in classical Islamic discourse has often led to uniform and authoritarian dress codes, particularly within Islamic educational institutions. This article proposes a new perspective on the concept of jilbab by referring to Muhammad Shahrur’s theory of hudud, which distinguishes between the minimum (hadd al-adna) and maximum (hadd al-a‘la) boundaries of Islamic law. This framework serves as a foundation for more flexible and contextual interpretations.Using qualitative analysis and literature review methods focused on Qur’anic verses An-Nur (24):31 and Al-Ahzab (33):59, this study explores how Shahrur’s thought can be applied to formulate inclusive Islamic educational policies—legally, pedagogically, and socio-culturally. The findings demonstrate that the hudud approach encourages critical and responsible interpretations of Islamic dress, offering opportunities to reform uniform policies, strengthen ethical values, and develop religious curricula that are responsive to social dynamics and gender equality issues.